2017
DOI: 10.1088/1674-1056/26/6/060308
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting phase qubits with shadow-evaporated Josephson junctions

Abstract: We develop a fabrication process for the superconducting phase qubits in which Josephson junctions for both the qubit and superconducting quantum interference device (SQUID) detector are prepared by shadow evaporation with a suspended bridge. Al junctions with areas as small as 0.05 µm 2 are fabricated for the qubit, in which the number of the decoherencecausing two-level systems (TLS) residing in the tunnel barrier and proportional to the junction area are greatly reduced. The measured energy spectrum shows n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…Epitaxial growth of Al on Si substrates has already been realized by ultrahigh vacuum (UHV)-based deposition techniques like molecular beam epitaxy (MBE) [10] or UHV evaporation [11,12]. However, UHV deposition systems are elaborate to operate and in general not well suited for JJ fabrication because shadow evaporation techniques [13,14] are difficult to implement. Up to now, high-vacuum (HV) electron-beam deposition systems, such as the Plassys MEB 550S system, are mainly used for JJ fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Epitaxial growth of Al on Si substrates has already been realized by ultrahigh vacuum (UHV)-based deposition techniques like molecular beam epitaxy (MBE) [10] or UHV evaporation [11,12]. However, UHV deposition systems are elaborate to operate and in general not well suited for JJ fabrication because shadow evaporation techniques [13,14] are difficult to implement. Up to now, high-vacuum (HV) electron-beam deposition systems, such as the Plassys MEB 550S system, are mainly used for JJ fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…While experimentally molecular oxygen (O 2 ), 5,26 ozone (O 3 ), 27 and both charged (O + ) 28,29 and neutral atomic oxygen (O) 30,31 can be used, it is known that O 2 has a large dissociation energy which the empirical potentials have not been designed to describe. 32 Campbell et al simulated the oxidation of nanoclusters and found similar behaviour for both neutral atomic oxygen and O 2 molecules excepting a change in the temperature at the surface.…”
Section: A Methodologymentioning
confidence: 99%
“…While experimentally molecular oxygen (O 2 ) 5,26 , ozone (O 3 ) 27 , and both charged (O + ) 28,29 and neutral atomic oxygen (O) 30,31 can be used, fully describing the adsorption of oxygen molecules on aluminium surfaces is an open problem. There is an ongoing discussion in the literature regarding the magnitude of the O 2 dissociation energy [32][33][34][35] and it is not known whether charge or spin dynamics play the dominant role 36 .…”
Section: Oxidation Of Aluminiummentioning
confidence: 99%